Pengaruh Strategi Pemasaran Dan Kepuasan Konsumen Terhadap Loyalitas Konsumen Fast Food McDonald’s Di Kota Malang - Saputra, Rizky Maulana; Farida, Eka; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the influence of marketing strategy and consumer satisfaction on McDonald's consumer loyalty in Malang City. The research method used is a quantitative research method. Sampling was carried out on McDonald's fast food consumers in Malang City using the Malhotra formula so that the sample obtained in this study was 50 respondents taken using a purposive sampling technique with criteria determined by the researcher. To obtain data, this research used a data collection method with a questionnaire. The data analysis used is instrument testing, normality testing, classical assumptions, multiple linear regression analysis, hypothesis testing, and coefficient of determination using the SPSS application. The results of this research show that marketing strategy and consumer satisfaction have a significant positive effect simultaneously on McDonald's consumer loyalty in Malang City. Furthermore, marketing strategy and consumer satisfaction partially have a significant positive effect on McDonald's consumer loyalty in Malang City. Keywords: Marketing Strategy, Consumer Satisfaction, Consumer Loyalty.